2010
DOI: 10.1299/jmmp.4.1496
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Applied Load Estimation Using Strain for Intelligent Tires

Abstract: From a traffic safety point of view, there is an urgent need for intelligent tires which can optimize braking control by estimating the slip ratio and friction coefficient between road surface and tire. In previous studies, we have proposed an application of strain data for estimating a friction coefficient. However, it only investigated the condition when the vertical or frictional loads changed but the other load remained constant. Since both of the frictional and vertical loads alter the measured strain dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 17 publications
(15 reference statements)
1
16
0
Order By: Relevance
“…Using strain signals acquired under dynamic conditions, distances between these points are calculated and result is in line with the measured static footprint of the tire. On this ground it is shown that existing techniques [13,14], which use the distance between the two extrema of the first time derivative of the strain, underestimates the footprint length. This marks a conceptual difference, suggesting the tire segments at the edges of the contact patch have the highest deformation acceleration in respect to the highest deformation speed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Using strain signals acquired under dynamic conditions, distances between these points are calculated and result is in line with the measured static footprint of the tire. On this ground it is shown that existing techniques [13,14], which use the distance between the two extrema of the first time derivative of the strain, underestimates the footprint length. This marks a conceptual difference, suggesting the tire segments at the edges of the contact patch have the highest deformation acceleration in respect to the highest deformation speed.…”
Section: Discussionmentioning
confidence: 99%
“…When the braking torque is applied, shear deformations due to the frictional load (18) arise and give rise to an asymmetrical strain distribution, as stated by Eqs. (13) [13], which predicts the strain induced by the frictional load is antisymmetric in respect to the centre of the footprint.…”
Section: Analytical Model For the Strain Distribution Over The Tire Smentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous study (33) proposed a concurrent estimating method for frictional and vertical loads applied to a tire from the tire strain data when both loads were changing. Finite element method (FEM) analysis was used for simulating tire deformation under various wheel loads and braking torques, and the relationship between the strain distribution and the applied loads were investigated.…”
Section: Introductionmentioning
confidence: 99%